Polymeric Ni(II) and Cu(II) complexes based on squaric acid and 1-vinylimidazole: Structural studies and hydrogen adsorption properties - Yilmaz, Hakan; Gorduk, Semih; Andac, Omer (ELSEVIER SCIENCE SA, 2018)
[M(sq)(vim)(2)(H2O)(2)](n) (M: Ni2+ and Cu2+ ions; sq: squarate dianion; vim: 1-vinylimidazole) complexes were crystallized, and characterized by elemental analysis, infrared spectroscopy (IR), thermal analysis, magnetic susceptibility, powder X-ray diffraction (PXRD) and X-ray single crystal techniques. The results of X-ray single crystal analysis demonstrate that both complexes crystallize in the monoclinic system with P2(1)/n space group and have slightly distorted octahedral geometries. In the complexes, the sq ligand behaves as bis(monodentate) via the oxygen atoms in trans-(mu-O-1,O-3) mode and the vim ligand coordinates to the metal ions via the ring nitrogen atom as monodentate. The complexes have one-dimensional (1D) polymeric chains constructed from the connecting of metal ions to each other by the sq ligands. The linking of 1D polymeric chains with the hydrogen bonds leads to the formation of two-dimensional (2D) supramolecular structures. The pi-pi interactions also contribute to the formation of three-dimensional (3D) supramolecular structures. The surface areas and hydrogen adsorption properties of the complexes were investigated. The accessible surface areas and free volumes of the complexes were also determined by theoretical calculations in 0.8 angstrom Connolly diameter. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Squarate dianion; 1-Vinylimidazole; Polymeric complex; Crystal structure; Hydrogen adsorption; METAL-ORGANIC FRAMEWORKS; COORDINATION POLYMERS; CRYSTAL-STRUCTURES; MAGNETIC-PROPERTIES; SQUARATO-METAL(II) COMPLEXES; DINUCLEAR COPPER(II); LIGANDS SYNTHESIS; NICKEL(II); TRINUCLEAR; STORAGE; Chemistry